Coaches' perspective, response, and influence of their athletes' emotional states during optimal and non-optimal performance - Salloman, Al Einstein Quindoza 1999-
Emotions are stimuli of an individual that directly affects sports performance leading to choking. Sports psychologists have struggled to formulate individual mental training approaches. Castellano et al. (2007) found an observable relationship between emotions and body movements. A central relationship in a sports team where interpersonal emotion regulation occurs is the coach and athlete. Moreover, coaches with higher emotional intelligence have better interpersonal skills. However, there is a lack of studies that paid attention to interpersonal emotion regulation in the coach and athlete relationship. Hence, this study tries to answer how coaches perceive their athletes’ emotional state in optimal and non-optimal sports performance. Using a qualitative design, seven UAAP table tennis coaches were interviewed. The objectives were to gather data on how coaches perceive, respond, and manage their athletes’ emotions. Deductive thematic analysis was used based on IZOF, using the modalities of bodily, motor-behavioral, operational, and communicative as codes along with the four branches of emotional intelligence. The study found that coaches perceive emotional states through the four modalities mentioned and respond by facilitating their own thoughts through emotions and understanding their athletes’ emotions. They then made attempts at interpersonal emotion regulation using positive reinforcements and scientific techniques they learned from experts. The study recommends including more participants, modalities, and other sports. It is also recommended to look into athletes’ perspectives, actual game experiences, and gender variations.